Genetic variability for seed yield and its components in Chickpea (Cicer arietinum L.) - Arvind Kumar; Suraj Kumar Gorian; Prashant Kumar Rai (Annals of Agricultural Research, 2024)
The present experiment was undertaken with eight genotypes of chickpea in a randomized block design (RBD) with three replications during rabi (2021 - 2022) at Agricultural Research Centre, Faculty of Agriculture, AISECT University- Hazaribag (Jharkhand). All the traits were recorded on the optimum plant growth stages. The data was recorded for eleven characters to study of genetic variability, genotypic and phenotypic coefficient of variance, heritability and genetics advance. Genotypic coefficient of variation (GCV) was highest for seed yield per plant followed by economic yield per plant except low Phenotypic coefficient of variation (PCV) of economic yield per plant, seed index (%), No of primary branches per plant, plant height, days to maturity, biological yield per plant, days to 50% flowering, harvest index (%), no of emergence per plant and no of pod per plant. Maximum heritability was observed for seed yield per plant (gm) followed by days to maturity, days to 50% flowering, seed index (%), economical yield per plant (gm), plant height (cm), no of emergence per plot, no of primary branches per plant, biological yield per plant (gm), harvest index and no of pod per plant. The genetic advance found was ranged from (0.13 to 10.53) with the highest estimate in case of days to maturity followed by economic yield per plant, days to 50% flowering, seed index (%), plant height, seed yield per plant, no of emergence per plot, no of primary branches per plant, harvest index (%) and no of pod per plant. High heritability and genetic advance indicate that the additive nature of gene action and reliability of those characters for selection and emerged as ideal traits for improvement through selection.